Nocardia Farcinica Lung Abscess Presenting in the Context of Advanced HIV Infection: Spontaneous Resolution in Response to Highly Active Antiretroviral Therapy Alone - Arienne S King; Jose G Castro; Gordon CK Dow (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 43-year-old man, known to be HIV-positive, presented with a six-week history of symptoms including cough, hemoptysis, anterior chest pain, fever and wasting. His CD4 cell count was 46 cells/μL, and his chest x-ray showed a cavitating lesion in the left upper lobe. Sputum culture was positive for Nocardia farcinica. His infection resolved following initiation of antiretroviral therapy. Nocardia is an uncommon opportunistic pathogen in patients with HIV infection and is usually associated with advanced CD4 depletion, cavitary pneumonia, metastatic infection and high mortality. The impact of antiretroviral therapy on Nocardia infection in the setting of HIV has not been clearly elucidated. The current report is the first to present a case in which a complete clinical cure of Nocardia pneumonia has been documented, primarily in response to highly active antiretroviral therapy alone.